INVESTIGATION OF NEAR-FIELD TEMPERATURE DISTRIBUTION IN BURIED DENSE PHASE CO2 PIPELINES - Olugunwa, Babafemi; Race, Julia; Yurtseven, Ahmet; Tezdogan, Tahsin (AMER SOC MECHANICAL ENGINEERS, 2021)
Buried pipelines transporting dense phase Carbon dioxide CO2 are crucial to carbon reduction and climate change mitigating technologies such as Carbon Capture and Storage (CCS) and Carbon Capture Utilization and Storage (CCUS). One of the major challenges for optimum pipeline operating conditions is to avoid phase change of the compressed CO2 and maintain temperature and pressure above the critical point throughout the pipeline route. A suitable pipe-soil heat transfer model during design can mitigate this challenge. However, variations in annual ambient temperatures, ground temperature at pipeline burial depth and soil temperature profile behaviors with seasonal climatic conditions especially during winter and summer periods also affect the heat transfer process between the soil burial medium and the CO2 pipeline. Assuming steady state, this paper investigates the nearfield temperature distribution up to 3m lateral distance away from a buried dense phase CO2 pipeline by numerical simulation with a two-dimensional pipe-soil heat transfer model at a burial depth of 2.3m to pipe center using a finite volume computational code. Results show that thermal parameters such as thermal conductivity and the soil temperature profile influence the heat exchange between pipe walls and porous soil medium. Consequently, this study shows that the near-field temperature distribution and effect of heat around a buried CO2 pipeline diminishes with distance and burial depth further away within the immediate vicinity of the pipeline.
Keywords: Buried CO2 pipeline; Near-field; Burial depth; Steady state; Temperature distribution; HEAT-TRANSFER; AMBIENT; Engineering